Displacement measurement technology of nano grating sensor based on HHT algorithm. (March 2021) - Jiang, Cuili; Tian, Zhihui; Yu, Wenjiao
Abstract: In order to improve the accuracy and stability of the displacement measurement of the nano-grating sensor, and to ensure that the measurement time is shorter, this paper proposes a nano-grating sensor displacement measurement technology based on the HHT algorithm. First, the HHT algorithm is used to sample the displacement data of the nano-grating sensor, and the interference signal is preprocessed. Among them, the CORDIC algorithm is used to subdivide the signal. Secondly, the HHT algorithm is used to effectively estimate the amplitude of the two detection signals that have been obtained. So far, the displacement measurement of the nano-grating sensor based on the HHT algorithm is completed. Finally, experiments are carried out, and the results show that the designed measurement technology can not only greatly shorten the measurement time, but also effectively ensure the output stability and accuracy of the measurement results, and effectively improve the work efficiency of the nano-grating sensor displacement measurement technology.